2020
DOI: 10.1177/0885328220956788
|View full text |Cite
|
Sign up to set email alerts
|

WE43 and WE43-T5 Mg alloys screws tested in-vitro cellular adhesion and differentiation assay and in-vivo histomorphologic analysis in an ovine model

Abstract: WE43 Mg alloy proved to be an ideal candidate for production of resorbable implants in both clinical and trial settings. In previous studies we tested biocompatibility and degradation properties of WE43 (as-cast) and artificially aged (WE43-T5) Mg alloys in a sheep model. Both alloys showed excellent biocompatibility with the as-cast, WE43, form showing increased degradability compared to the artificially aged, WE43-T5. In the present study, our group assessed the biological behavior and degradation pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The detailed pre-clinical studies of these alloys were summarized in Table 1. [52] pin Rat femoral bones 7 days 0.15 ± 0.03 mm/y 26 Mg enriched (>99 wt.%) [53] pin Rat femoral bones 4, 24, 52 weeks 16 ± 5 µm/y Pure Mg high pressure (99.98 Mg in wt.%) [54] disk Rat femoral bones 24 weeks 0.41 ± 0.02 mm/y WE43 (>92.0 Mg in wt.%) [55] plates and screw Dogs-LeFort I osteotomy 4, 12, and 24 weeks NA 1 WE43 (>92.0 Mg in wt.%) [56] screw Rabbit tibiae 4, 8, 12 and 16 weeks NA 1 WE43 (>92.0 Mg in wt.%) [57] pin Rat tibiae 52 weeks NA 1 WE43/WE43T5 (>92.0 Mg in wt.%) [58] screw Sheep mandibule 6 and 24 weeks NA 1 MgYREZr (>92.0 Mg in wt.%) [59] screw Rabbit femoral bones 1, 12, and 52 weeks NA 1 JDBM (>95.0 Mg in wt.%) [60] screw Rabbit mandible bones 1, 4, and 7 months 0.161 ± 0.025 mm/y (1 month), 00.218 ± 0.030 mm/y (7 months) NZK (>96.0 Mg in wt.%) [61] rod Rabbit femoral bones 28 and 56 days 0.66 mm/y (28 days) and 0.48 mm/y (56 days) Mg-Zn (94.0 Mg in wt.%) [62] rod Rabbit femoral bones 14 weeks 2.32 mm/y ZX00 (>99.0 Mg in wt.%) [63] pin Rat femoral bones and sheep tibiae 6, 12 and 24weeks 0.08 mm/y (rat) and 0.045 mm/y (sheep) ZX00 (>99.0 Mg in wt.%) [64] screw Sheep tibiae 3, 6 and 12 weeks NA 1…”
Section: Mg and Its Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed pre-clinical studies of these alloys were summarized in Table 1. [52] pin Rat femoral bones 7 days 0.15 ± 0.03 mm/y 26 Mg enriched (>99 wt.%) [53] pin Rat femoral bones 4, 24, 52 weeks 16 ± 5 µm/y Pure Mg high pressure (99.98 Mg in wt.%) [54] disk Rat femoral bones 24 weeks 0.41 ± 0.02 mm/y WE43 (>92.0 Mg in wt.%) [55] plates and screw Dogs-LeFort I osteotomy 4, 12, and 24 weeks NA 1 WE43 (>92.0 Mg in wt.%) [56] screw Rabbit tibiae 4, 8, 12 and 16 weeks NA 1 WE43 (>92.0 Mg in wt.%) [57] pin Rat tibiae 52 weeks NA 1 WE43/WE43T5 (>92.0 Mg in wt.%) [58] screw Sheep mandibule 6 and 24 weeks NA 1 MgYREZr (>92.0 Mg in wt.%) [59] screw Rabbit femoral bones 1, 12, and 52 weeks NA 1 JDBM (>95.0 Mg in wt.%) [60] screw Rabbit mandible bones 1, 4, and 7 months 0.161 ± 0.025 mm/y (1 month), 00.218 ± 0.030 mm/y (7 months) NZK (>96.0 Mg in wt.%) [61] rod Rabbit femoral bones 28 and 56 days 0.66 mm/y (28 days) and 0.48 mm/y (56 days) Mg-Zn (94.0 Mg in wt.%) [62] rod Rabbit femoral bones 14 weeks 2.32 mm/y ZX00 (>99.0 Mg in wt.%) [63] pin Rat femoral bones and sheep tibiae 6, 12 and 24weeks 0.08 mm/y (rat) and 0.045 mm/y (sheep) ZX00 (>99.0 Mg in wt.%) [64] screw Sheep tibiae 3, 6 and 12 weeks NA 1…”
Section: Mg and Its Alloysmentioning
confidence: 99%
“…At 24 weeks, histomorphological analysis showed that WE43-T5 alloy had higher degradation rate and enhanced bone remodelling compared to WE43 (as-cast). Therefore, the developed WE43-T5 alloy is a suitable candidate as an endosteal bone screw [ 58 ]. Another in vivo study carried out by Byun et al concluded that extruded WE43 was suitable to be used for mid-facial application.…”
Section: Mg and Its Alloysmentioning
confidence: 99%
“…Therefore, magnesium regained relevance for clinical use in load-bearing applications of reconstructive and trauma surgery. Several in vivo preclinical studies successfully observed new bone deposition around WE43 plates and screws (Schaller et al, 2016;Naujokat et al, 2017;Byun et al, 2020;Imwinkelried et al, 2020;On et al, 2020;Rendenbach et al, 2021;Torroni et al, 2021) and a preserved structural integrity in the first 12 weeks of the healing process (Marukawa et al, 2016;Levorova et al, 2018). However, to date, only Leonhardt et al (Leonhardt et al, 2017;Leonhardt et al, 2021) reported a clinical application of magnesium-based lag screws for mandibular condylar head fracture fixation.…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with current trends in tissue engineering that use biomaterials to facilitate autologous tissue engineering in vivo. The use of bioceramic, alloy and nanomaterial implants to promote bone regeneration using the in vivo environment as a bioincubator has already shown promise in animal fracture repair models [84,85].…”
Section: In Vivo Implantation Of Cellularized Poss-pcl-fibrin Promote...mentioning
confidence: 99%